2019
DOI: 10.1021/acsami.9b12545
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Electrodeposition Enabling the Programmable Three-Dimensional Growth of a Multimodal Room Temperature Nanobridge Gas Sensor Array

Abstract: Parallel three-dimensional (3D) growth of different nanomaterials with submicrometer resolution is a promising approach to overcome some technological and economic limits encountered in planar integrated homogeneous films. The programmable multimaterial gas phase nanoparticle electrodeposition concept enables the fabrication of a 3D multimodal conductometric gas sensor array. The approach requires the deposition of more than one nanomaterial to achieve orthogonal sensing capabilities and multigas sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The phenomenon of next neighbor interaction is caused by Coulombic coupling of the next nearest neighbor openings described recently. 28,29 Reference experiments revealed that without the corona charger, this deposition mode could not be achieved (see Supporting Figure S3, comparison of the deposition without and with a corona charger).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of next neighbor interaction is caused by Coulombic coupling of the next nearest neighbor openings described recently. 28,29 Reference experiments revealed that without the corona charger, this deposition mode could not be achieved (see Supporting Figure S3, comparison of the deposition without and with a corona charger).…”
Section: Resultsmentioning
confidence: 99%
“…Here, an alternative parallel deposition approach is introduced as a further development of the localized particle deposition. The knowledge gained in the field of particles is now applied to precursor molecules. Specifically, an electrically charged and guided molecular flux is reported instead of charged nanoparticles.…”
mentioning
confidence: 99%
“…Gas sensors with MOX-type film have been successfully commercialized because they can be mass produced, exhibit good uniformity, and enable reliable gas sensing . The film-based MOX can be synthesized via the sol–gel process, sputtering, evaporation, electrodeposition, or chemical vapor deposition . However, sputtering is widely used for manufacturing film-type sensing materials owing to its simplicity, room-temperature (RT) processability, and mass production capabilities .…”
Section: Introductionmentioning
confidence: 99%
“…In this process, metallic nanoparticles are generated in a spark discharge, transported to the substrate by a gas flow, and can subsequently be deposited into layers [ 17 ] or localized structures. [ 13–15,18–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…In this process, metallic nanoparticles are generated in a spark discharge, transported to the substrate by a gas flow, and can subsequently be deposited into layers [17] or localized structures. [13][14][15][18][19][20] While the benefits of material conservation, size reduction through lensing, and surrounding airgaps are beneficial, the process of gas phase electrodeposition has so far been limited by less electrical conductance. The formation of desired 3D shapes that grew out of the charge dissipating openings under the influence of the dynamic evolving lensing funnel like electric field, consist of small metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%